Evaluation of the International Finance Corporation's Global Trade Finance Program, 2006-12 - WorldBank (World Bank, 2015)
As part of its strategy to support global trade, the World Bank Group seeks to enhance trade finance in emerging markets. In 2005 the International Finance Corporation (IFC), part of the Bank Group, introduced the Global Trade Finance Program (GTFP) to support the extension of trade finance to underserved clients globally.